Nanoparticle-based Gene Therapy for Neurodegenerative Disorders - Ereej, Nelofer; Hameed, Huma; Khan, Mahtab A.; Faheem, Saleha; Hameed, Anam (Mini Reviews in Medicinal Chemistry, 2024)
Neurological disorders present a formidable challenge in modern medicine due to the intricate obstacles set for the brain and the multipart nature of genetic interventions. This review article delves into the promising realm of nanoparticle-based gene therapy as an innovative approach to addressing the intricacies of neurological disorders. Nanoparticles (NPs) provide a multipurpose podium for the conveyance of therapeutic genes, offering unique properties such as precise targeting, enhanced stability, and the potential to bypass blood-brain barrier (BBB) restrictions. This comprehensive exploration reviews the current state of nanoparticle-mediated gene therapy in neurological disorders, highlighting recent advancements and breakthroughs. The discussion encompasses the synthesis of nanoparticles from various materials and their conjugation to therapeutic genes, emphasizing the flexibility in design that contributes to specific tissue targeting. The abstract also addresses the low immunogenicity of these nanoparticles and their stability in circulation, critical factors for successful gene delivery. While the potential of NP-based gene therapy for neurological disorders is vast, challenges and gaps in knowledge persist. The lack of extensive clinical trials leaves questions about safety and potential side effects unanswered. Therefore, this abstract emphasizes the need for further research to validate the therapeutic applications of NP-mediated gene therapy and to address nanosafety concerns. In conclusion, nanoparticle-based gene therapy emerges as a promising avenue in the pursuit of effective treatments for neurological disorders. This abstract advocates for continued research efforts to bridge existing knowledge gaps, unlocking the full potential of this innovative approach and paving the way for transformative solutions in the realm of neurological health.
Keywords: neurological disorders